Managing and developing distributed research projects in software engineering by means of action-research - Francisco J. Pino (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
Participation in software research projects involving several organizations (research groups, enterprises, etc) scattered all around the world is an increasingly frequent phenomenon. The geographical distribution of the organizations entails the research projects development and management taking suitable Software Engineering research methods which must satisfy the acquired commitments as well as the new coming challenges. In that respect, this paper discusses how the Action-research qualitative method can be suitable for managing and developing software engineering distributed research projects. Furthermore, we propose a strategy to guide the use of Action-research in the context of distributed research projects. The application of this strategy in a research project, in which more than 10 enterprises and 27 research groups from 13 countries from Latin-America plus Portugal and Spain took part, is also illustrated. We observed that the use of the proposed strategy was able to provide the research managers with: (i) a suitable research project centralized administration, and (ii) appropriate coordination and apportioning of the research responsibilities for the research products construction and validation. It is important to highlight that the proposed strategy is a new way of applying the Action-research method in Software Engineering